FINDING THE OPTIMAL SOLUTION TO ALGORITHMIC PROGRAMMING ISSUES THROUGH GRAPHS - M. K. Movlonov (Zeta Repository, 2023)
This article discusses the problem of finding the optimal solution to economic processes using mathematical modeling, specifically the linear programming problem, through graphical methods.